The Science of Stephen King : - Gresh, Lois H. (John Wiley & Sons, 2007)
"The Science of Stephen King appeals to both the scientist and the longtimereader of Stephen King in me. Gresh and Weinberg use concepts from King's fiction as launching pads for in-depth explorations of concepts as diverse as ESP, pyrokinesis, time travel, artificial intelligence, quantum chemistry, alternate realities, string theory, and the possibility that we'll be visited by aliens or that we'll face a global pandemic. Much of what Stephen King writes about in his novels is closer to reality than you might think."